2023
DOI: 10.3390/ph16030406
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Analysis of Drug Inhalation in Realistic Human Upper Airway Model

Abstract: The demand for a more efficient and targeted method for intranasal drug delivery has led to sophisticated device design, delivery methods, and aerosol properties. Due to the complex nasal geometry and measurement limitations, numerical modeling is an appropriate approach to simulate the airflow, aerosol dispersion, and deposition for the initial assessment of novel methodologies for better drug delivery. In this study, a CT-based, 3D-printed model of a realistic nasal airway was reconstructed, and airflow pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Aasgrav et al [3] showed that laminar and RANS CFD models produced similar results. The conclusion has been supported by many researchers including, e.g., Larimi et al [199], who reported negligible turbulence intensity in the nasal cavity for normal, inspiratory breathing rates, and Schillaci and Quadrio [148] and Bradshaw et al [159], who reported mostly laminar flow for normal resting breathing conditions.…”
Section: Modelling Approaches In In Silico Studiesmentioning
confidence: 69%
See 1 more Smart Citation
“…Aasgrav et al [3] showed that laminar and RANS CFD models produced similar results. The conclusion has been supported by many researchers including, e.g., Larimi et al [199], who reported negligible turbulence intensity in the nasal cavity for normal, inspiratory breathing rates, and Schillaci and Quadrio [148] and Bradshaw et al [159], who reported mostly laminar flow for normal resting breathing conditions.…”
Section: Modelling Approaches In In Silico Studiesmentioning
confidence: 69%
“…Also, the current paper does not review the extensive scientific literature concerning FSI, acoustic phenomena, or particle transport and deposition, in human airways. Recent literature overviews on these topics were provided by Ashraf et al [ 107 ] and Le et al [ 197 ] for FSI, Xi et al [ 198 ] for acoustics, and Larimi et al [ 199 ] for particle deposition.…”
Section: Part Ii—overview Of Published Literature On In Vitro and In ...mentioning
confidence: 99%
“…Measurements based on computational fluid dynamics (CFD) have been the subject of studies demonstrating the method’s effectiveness [ 8 , 9 , 10 , 11 ]. Numerical analysis has been used in various studies such as airflow diagnostics in patients with sleep apnoea, deposition fraction, and drug delivery efficiency [ 12 , 13 ]. Recent research has confirmed that the use of numerical modelling to analyse airflow through the nasal cavity (virtual rhinomanometry) can be considered a reliable method [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through the digital model, the analysis and computation of parameters such as pressure, velocity, and turbulent kinetic energy (TKE) can be compared with other models. Additionally, the study [20] showed that there was tissue displacement and hypoplasia for patients with cleft lip repair. Therefore, the authors proposed 3Dprinted autologous cartilage rhinoplasty to reconstruct the nasal shape.…”
Section: Introductionmentioning
confidence: 99%